MELO, Hildete Pereira de; RODRIGUES, Lígia Maria C. S. Pioneiras da ciência no Brasil. - Veiga, Ana Maria (Revista Estudos Feministas, 2006)
MELO, Hildete Pereira de; RODRIGUES, Lígia Maria C. S. Pioneiras da ciência no Brasil.